Post-exercise Hypotension Produced by Supramaximal Interval Exercise is Potentiated by Angiotensin Receptor Blockers - Ramirez-Jimenez, Miguel; Morales-Palomo, Felix; Ortega, Juan Fernando; Mora-Rodriguez, Ricardo (International Journal of Sports Medicine, 2019)
We studied the effects of supramaximal interval exercise (SIE) with or without antihypertensive medication (AHM) on 21-hr blood pressure (BP) response. Twelve hypertensive patients chronically medicated with AHM, underwent three trials in a randomized order: a) control trial without exercise and substituting their AHM with a placebo (PLAC); b) placebo medicine and a morning bout of SIE (PLAC+SIE), and c) combining AHM and exercise (AHM+SIE). Acute and ambulatory blood pressure responses were measured for 21-hr after treatment. 20  min after treatment, systolic blood pressure (SBP) readings were reduced, similar to readings after PLAC+SIE (−9.7±6.0 mmHg, P<0.001) and AHM+SIE (−10.4±7.9 mmHg, P=0.001). 21 h after treatment, SBP remained reduced after PLAC+SIE (125±12 mmHg, P=0.022) and AHM+SIE (122±12 mmHg, P=0.013) compared to PLAC (132±16 mmHg). The BP reduction in PLAC+SIE faded out at 4 a.m., while in AHM+SIE it continued overnight. At night, BP reduction was larger in AHM+SIE than PLAC+SIE (–5.6±4.0 mmHg, P=0.006). Our data shows that a bout of supramaximal aerobic interval exercise in combination with ARB medication in the morning elicits a sustained blood pressure reduction lasting at least 21-h. Thus, the combination of exercise and angiotensin receptor blocker medication seems superior to exercise alone for acutely decreasing blood pressure.
Keywords: antihypertensive drugs; metabolic syndrome X; aerobic exercise; high blood pressure; hypertension.